Effect of bacterial virulence on IL-18 expression in the amnion infected with Escherichia coli - Splíchalová, Alla; Trebichavský, Ilja; Muneta, Yoshihiro; Mori, Yasuyuki; Splíchal, Igor (American journal of reproductive immunology (New York, N.Y., 2005)
PROBLEM: The upregulation of inflammatory substances threatens pregnancy. Interleukin-18 (IL-18) is elevated in women who miscarried. The purpose of this study was to develop a pig model of chorioamnionitis to study the effect of bacterial virulence on IL-18 response in experimentally infected amnion. METHOD OF STUDY: A total of 20,000 colony-forming units of Escherichia coli (an enteropathogenic O55 strain, EPEC or O86 non-pathogenic strain) were administered into the amniotic cavity of pig fetuses at 70% of gestation for 10 hr. Fetal amniotic fluid samples were analyzed for IL-18 levels by enzyme-linked immunosorbent assay. The expression of IL-18 was studied also by immunohistochemistry on cryostat sections through amniotic membranes and pathological changes were observed by electron microscopy. RESULTS: Both E. coli strains propagated in amniotic fluids and reached similar counts. Only EPEC, however, caused a significant increase of IL-18 amniotic fluid levels (P < 0.001) and cytokine expression in the amniotic epithelium. CONCLUSIONS: The levels of IL-18 in infected amniotic fluids correlated with bacterial virulence and pathological changes in the amnion.
Keywords: Virulence; interleukin-18; Animals; Microscopy, Electron, Transmission; Escherichia coli Infections; Female; infekce vyvolané Escherichia coli; Escherichia coli; ženské pohlaví; Immunohistochemistry; fluorescenční protilátková technika; těhotenství; prasata; Fluorescent Antibody Technique; imunohistochemie; virulence; Swine; amnion; transmisní elektronová mikroskopie; zvířata; Interleukin-18; Pregnancy; Amnion